Electronic Cigarettes: A Growing Threat of Oral Squamous Cell Carcinoma in Young Adults? - Thayná Assencio Pereira Aguiar; Raianny de Souza Santos; Sara Rocha Moraes Sousa; Anna Clara de Matos Marçal; Isnaya Almeida Brandão Lima; Ana Cláudia Garcia Rosa (Essentials of Dentistry)
Electronic cigarettes are widely used by young adults, yet their impact on oral health, specifically in the context of oral squamous cell carcinoma (OSCC), is poorly understood. This study aimed to evaluate the association between e-cigarette use and OSCC incidence in young adults. An integrative literature review was conducted using the PICO framework. Databases, such as PubMed and Google Scholar, were searched for studies published between 2020 and 2024. Observational studies, controlled trials, systematic reviews, and meta-analyses were included. Quality assessment was performed using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. This review found evidence of DNA damage, cellular changes, and increased cell proliferation associated with e-cigarette use, which may contribute to the development of OSCC. However, these studies have shown mixed results regarding the direct increase in OSCC incidence, indicating the need for further research. In conclusion, while there is some indication of the carcinogenic potential of e-cigarettes, further research is necessary to establish a definitive link. This review supports the need for stricter regulations and increased awareness of the risks associated with e-cigarette use among young adults. Public health policies should reflect these findings to reduce the risks associated with vaping.